Southern Romance: Relationship Quality, Consensus, and Context among Cohabiting Couples in the Gulf States. Issue 2 (17th February 2020) - Harris, Victor W.; Visconti, Brian; Sewell, Charles B.; Cantrell, Randall; Anderson, Jon; Davison, Emily M.
Abstract: Relationships are significantly stressed in the Southeastern United States. Of the six states in the Gulf region (Florida, Georgia, Alabama, Mississippi, Louisiana, and Texas), four are in the top-third of the nation's highest divorce rates. Threats to relationship household stability cause a myriad of social problems and public expenses of approximately 24 billion in increased spending in benefit programs to offset family hardship following divorce and relationship dissolution. This study analyzed associations between relationship quality and satisfaction, consensus, and a series of contextual variables among three types of cohabiting homeowners across the Gulf States (unmarried, married, and married with additional family members), surveying variables of interest. Findings indicated that dyadic couple relationships in this sample are generally distressed relative to other states and that significant negativity is present, but that a large portion of the variance in relationship quality is consistently predicted by certain factors. Using an instrument of increased sensitivity, these factors (consensus, negative interaction, household composition, etc.) have been parsed into specific components (types of consensus, types of interaction, etc.) for improved individual analysis. Specific relationship problem areas are outlined, clarified, and discussed.